The effect of heavy metal contamination on humans and animals in the vicinity of a zinc smelting facility - Shen, Xiaoyun; Chi, Yongkuan; Xiong, Kangning (PloS one, 2019)
A diagnosis of heavy metal poisoning in sheep living on pastures in the vicinity of a smelting facility in the Wumeng mountain area of China was based on laboratory tests and clinical symptoms. Furthermore, heavy metal contamination in the food chain was found to have a deleterious effect on the health of local residents. The levels of copper(Cu), zinc(Zn), cadmium (Cd), and lead (Pb) in irrigation water, soil, forages, and animal tissues were measured in samples taken from the vicinity of a smelting facility and control samples. Heavy metal contents in food (corn, rice, and wheat), as well as in human tissues (blood and hair) obtained from local residents were also determined. Hematological values were also determined in human and animal samples. The content of Cu, Zn, Cd, and Pb in irrigation water, soils, and forages were markedly higher in affected areas than in samples from healthy pastures. Concentrations of Cd and Pb were 177.82 and 16.61 times greater in forages than controls, respectively, and 68.71 and 15.66 times greater in soils than controls, respectively. The heavy metal content in food (corn, rice, and wheat) from affected areas was markedly higher than in the control samples. Cd and Pb content in the tissues of affected sheep were markedly higher than in control animals (P < 0.01), while concentrations of Cd and Pb in blood and hair samples from local residents were markedly higher than in control samples (P < 0.01). The occurrence of anemia in affected humans and animals followed a hypochromic and microcytic pattern. The intake of Cd and Pb was estimated according to herbage ingestion rates. It was found that the levels of Cd and Pb which accumulated in sheep through the ingestion of vegetation growing in the sites closest to the smelter were approximately 3.36 and 38.47 mg/kg body wt./day, respectively. Such levels surpassed the fatal dosages for sheep of 1.13 mg Cd/kg body wt/day and 4.42 mg Pb/kg body wt./day. The serum total antioxidant capacity in affected humans and animals was significantly lower than in the controls (P < 0.01). Serum protein parameters in affected humans and animals were significantly reduced (P < 0.01); therefore, it was concluded that heavy metal contamination caused harm to sheep, and also posed a significant risk to humans living in the vicinity of the zinc smelting facility.